P49 How to translate an advance care planning (ACP) conversation in a future care treatment plan? The ACP-NOPA web application. Issue Volume 9: Issue (2019)Supplement 2 (3rd December 2019) - Loupatatzis, B; Karzig, I; Obrist, M; Otto, Th; Weber, A; Krones, T
Abstract : Background: The application was developed 2016 in Switzerland. The tool combines the different concepts of ACP, shared decision making (SDM) and medical emergency planning. In step one all documents and decision aids to create a living will are provided. Depending on the specifications the patient made in the living will (especially concerning treatment intensity and last-place-of-care) during step 2 the tool supports the care team in discharge management and/or creating emergency plans. The underlying illness of the patient is considered by providing the likely symptoms and giving treatment suggestions for the case of an emergency situation. Methods: The tool and the underlying educational program were developed based on our experiences with the MAPS –trial (a randomized controlled trial) and palliative emergency planning to support professional care givers in conducting an ACP conversation and creating a living will based on SDM and to translate both in concrete treatment planning and future treatment planning in case of decisional incapacity. The tool was implemented in the Kanton of Zurich and tested in a feasibility study with piloting teams. Results: We will present our concept and the results of the feasibility study. Discussion: Core competences of ACP, SDM, intensive and palliative care are combined in this web application to support professional care givers in creating highly individualized emergency treatment plans for severely ill, multimorbid or elderly nursing home patients. Providing caregivers with these combined competences is a good way to help patients to get their treatment of choice in their favorite place-of care.